2004
DOI: 10.1007/s00253-004-1594-6
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a gluconate/polyol dehydrogenase gene from Gluconobacter suboxydans IFO 12528, characterisation of the enzyme and its use for the production of 5-ketogluconate in a recombinant Escherichia coli strain

Abstract: A 5-ketogluconate (5-KGA)-forming membrane quinoprotein, gluconate dehydrogenase, was isolated from Gluconobacter suboxydans strain IFO 12528 and partially sequenced. Partial sequences of five internal tryptic peptides were elucidated by mass spectrometry and used to isolate the two adjacent genes encoding the enzyme (EBI accession no. AJ577472). These genes share close homology with sorbitol dehydrogenase from another strain of G. suboxydans (IFO 3255). Substrate specificity of gluconate 5-dehydrogenase (GA 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…This hypothesis was subsequently refuted when 18 O tracer experiments suggested the cleavage mechanism to involve a putative hydrolase (18). More recently (19), it has been shown that, in Gluconobacter suboxidans, 5-keto D-gluconic acid can be used as the substrate for a dedicated transketolase. These authors speculated that further oxidation of the resulting four-carbon semialdehyde by a succinate semialdehyde dehydrogenase homolog could result in formation of TA.…”
mentioning
confidence: 99%
“…This hypothesis was subsequently refuted when 18 O tracer experiments suggested the cleavage mechanism to involve a putative hydrolase (18). More recently (19), it has been shown that, in Gluconobacter suboxidans, 5-keto D-gluconic acid can be used as the substrate for a dedicated transketolase. These authors speculated that further oxidation of the resulting four-carbon semialdehyde by a succinate semialdehyde dehydrogenase homolog could result in formation of TA.…”
mentioning
confidence: 99%
“…The K m values of PQQ-GLDH are rather high (20,40, and 420 mM for D-arabitol, D-sorbitol, and GA, respectively [10]). 5KGA is a useful compound as a precursor of tartaric acid, xylaric acid, or a number of flavor compounds (18); thus, several attempts to produce 5KGA have been made with Glu-conobacter strains, and recently, exclusive production of 5KGA was accomplished with an FAD-GADH-defective mutant of Gluconobacter oxydans 621H (5). On the other hand, 2KGA itself is also a useful chemical and is applicable as a building block in the chemical synthesis of heterocyclic compounds and for regioselective and stereoselective chemical reactions (23).…”
mentioning
confidence: 99%
“…5KGA is a useful raw material for the production of tartaric acid and xylaric acid and is used as a precursor for the synthesis of a number of flavor compounds, including 4-hydroxy-5-methyl-2,3-dihydrofuranone-3 (15). Moreover, it has been reported that 5KGA can be used to produce vitamin C by Gray's method (6,7), which is different from Reichstein's method, which is now commonly used in industry.…”
mentioning
confidence: 99%